Understanding Mid-Term Immobilization Patterns of Soluble Pb in Soils Treated with Natural Geo-Sorbents : Laboratory Trial with Ultisols from a Montane Forest, Sri Lanka - Kasun Lakmini; Niluka Ranasinghe; Rasanjali Jayamuni de Silva; Priyantha Indralal Yapa; Ranmalee Bandara; Mahinda Senevirathne (Journal of Forest and Environmental Science, 2025)
The quick expansion of forest dieback in Horton Plains (HP), a cloud forest in Sri Lanka, is now a major concern. Lead (Pb) accumulated in the forest soil has been identified as one of the major culprits behind the forest dieback in HP. Natural geo-sorbents like biochar plays a vital role in remediating soils contaminated with heavy metals, via the adsorption heavy metals into sorption sites. This research focused on understanding the mid-term immobilization patterns of available Pb in HP soils treated with natural geo-sorbents. The treatments were: (T1) rubber-nut shell biochar (BRS), (T2) rice husk biochar (BHS), (T3) dead wood (from HP) biochar (HPS), and (T4) HP forest soil only (CS). Soil and dead wood were separately collected from HP and taken to a laboratory. All soil samples were spiked to show over 300 ppm of soil available Pb, geo-sorbents added where appropriate, and incubated at room temperature. HP soils were high in soil organic matter (SOM) (13.4%) with low pH (5.4). During the initial 3 months of the experiment, HPS recorded the lowest immobilization compared to BRS and BHS, with the latter having the highest immobilization. Yet, at the end of 18 months, all treatments showed the capacity to almost completely immobilize (∼96%) soil available Pb. As such, it can be concluded that (i) maintaining increased levels of SOM, and/or (ii) conditioning the soil with a natural geo-sorbent like biochar can help immobilize Pb in a forest with Ultisols.